Behavioral Genetic Approaches and Family Theory. Issue 1 (4th March 2014) - Moore, Ginger A.; Neiderhiser, Jenae M.
<x xml:space="preserve">Abstract</x> Family theories have been founded on research that cannot discriminate genetic and environmental influences and, consequently, most theories do not have highly developed models of gene–environment interplay in families. Behavioral genetic approaches, which can identify gene–environment interplay, have typically not been driven by family theories and have lacked adequate measurement of family processes. In this article, the authors describe behavioral genetic mechanisms and methods using representative examples of research on family processes, highlighting the advantages of an integrated approach. New directions in research and theory driven by an integrated approach are discussed.